Effect of heat treatment on the wear and corrosion behaviors of a gray cast iron coated with a colmonoy 88 alloy deposited by high velocity oxygen fuel (HVOF) thermal spray - (:unkn) unknown (My University, 2013)
The present work has been conducted in order to determine the influence of heat treatment on the wear and corrosion behaviours of a gray cast iron substrate coated with a Ni base coating deposited by HVOF thermal spray. The wear resistance of the coatings was obtained using a reciprocating wear tester by rubbing a 10 mm diameter steel ball on the coatings at normal atmospheric conditions. Corrosion tests were performed using potentiodynamic polarization measurements in a 3,5 % NaCl solution. It was observed that the corrosion and wear resistance of the coatings increased along with the reduction of porosity and roughness by the heat treatment.
Keywords: Corrosion; HVOF; Ni-based coating; Post-heat treatment; Wear